Perda de participação do emprego industrial e evolução do setor comercial no Brasil - Nakabashi, Luciano; Porcile, Gabriel; Cruz, Márcio José Vargas da; Scatolin, Fábio Dória (Revista Economia & Tecnologia, 2007)
*